Functional Interactions between Stress and the Endocannabinoid System: From Synaptic Signaling to Behavioral Output - Hill, Matthew N. (Society for Neuroscience, 2010)
Endocannabinoid signaling is distributed throughout the brain, regulating synaptic release of both excitatory and inhibitory neurotransmitters. The presence of endocannabinoid signaling within stress-sensitive nuclei of the hypothalamus, as well as upstream limbic structures such as the amygdala, suggests it may play an important role in regulating the neuroendocrine and behavioral effects of stress. The evidence reviewed here demonstrates that endocannabinoid signaling is involved in both activating and terminating the hypothalamic-pituitary-adrenal axis response to both acute and repeated stress. In addition to neuroendocrine function, however, endocannabinoid signaling is also recruited by stress and glucocorticoid hormones to modulate cognitive and emotional processes such as memory consolidation and extinction. Collectively, these data demonstrate the importance of endocannabinoid signaling at multiple levels as both a regulator and an effector of the stress response.